REVOLUSI ILMIAH THOMAS SAMUEL KÜHN (1922-1996) DAN RELEVANSINYA BAGI KAJIAN KEISLAMAN - Mu'ammar Zayn Qadafy (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2014)
Through his Structure of Revolution, Thomas Kühn contributed a big movement, not only in the philosophy of science, but also in social as well as natural and religious sciences. This article is written to elaborate the epistemological aspects of Kühn’s philosophy from for keywords: paradigm, objectivity of science, scientific community and revolution of sciences. This research concludes that Kühn, responding Auguste Comte’s positivism and Popper’s Falsificasionarism, compelled a revolutionary development of science despite the linear-accumulative one. For him, knowledge is never objective (value-neutral) for its being from a particular consensus in a particular paradigm. Therefore, scientific method has to appropriate with the cycle of scientific revolution (normal science – anomalies – crisis - extraordinary science – revolution - normal science 2, etc.) In Kühn’s, truth does not depend totally on any method used to test it. It depends on acknowledgement of some subjectivities in a knowledge. Although sciences, for him, are not comparable, science in the last paradigm is more consistent, accurate, and useful. Kühn’s philosophy is relevant with current issues on Islamic studies, namely paradigm shifting of Islamic epistemology, membership of religious scholars community and paradigm of Islam’s Jumhur.